Vibrio pathogenicity island and phage CTX genes in Vibrio alginolyticus isolated from different aquatic environments. (7th October 2022) - Khouadja, Sadok; Roque, Ana; Gonzalez, Mar; Furones, Dolors
Abstract: In the present study, we investigated the presence of four Vibrio cholerae virulence genes ( ctxA, VPI, Zot and ace ) in 36 Vibrio alginolyticus isolates obtained from different seawater, sediments and aquatic organisms. We tested the virulence of 13 V. alginolyticus strains against juveniles of Sparus aurata and this virulence was correlated with the presence of V. cholerae virulence genes. A positive amplification for the virulence pathogenicity island was produced by five V. alginolyticus strains and four for cholerae toxin. Some of the V. alginolyticus strains are pathogenic to aquatic animals and might have derived their virulence genes from V. cholerae . V. alginolyticus strains can be considered as a possible reservoir of V. cholerae virulence genes. HIGHLIGHTS: We investigated the presence of virulence genes in Vibrio alginolyticus strains. We detected the presence of the virulence markers VPI and ctxA . Strains showing VPI genes were found virulent for Sparus aurata . Graphical Abstract